Axiological Dimensions of the Value of Harmony for Javanese Society - Sahfutra, Suryo Adi; Septiana Dwiputri Maharani (Andalas International Journal of Socio-Humanities, 2022)
The background of this study begins with a reflective question about why in one family Indonesian people of different religions can live in harmony and support each other as a family. Whereas in the social context of religious relations today faces a tense situation in which people of different religions are suspicious of each other and hostile to each other. This study tries to focus on the case of Javanese families who have the foundation of the value of living in harmony in one family with different religions from an axiological perspective. Based on the interpretation approach to social phenomena that are the focus of the study. The results of this study explain that the foundation of the value of harmony of Javanese people lies in the value of harmony, which is an integral principle of value in which Javanese who wants to live a harmonious life must maintain harmony not only with others but also with the surrounding nature. Therefore, many studies have shown that Javanese life always tries to maintain ‘equilibrium’ as a manifestation of life. The axiological dimension of the living value of Javanese harmony when meeting with external values occurs tug-of-war and it is not uncommon to negate each other and contest each other. In some cases, it is proven that the value of living in harmony can support a harmonious family life, getting along well with mutual respect, affection, and mutual help among family members.